2004
DOI: 10.1597/03-019.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Spanish Language Educational Materials by American Cleft Palate–Craniofacial Association Teams

Abstract: Many U.S.-based ACPA teams reported an increase in primarily Spanish speakers and expressed a need for more Spanish-language educational materials in different formats. Consideration of the diverse dialectic, cultural, and literacy needs of U.S. Spanish speakers can contribute to more effective educational efforts and improved care of the increasing number of Latinos treated by ACPA teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…In a second study, Edward and Bonilla (2004) examined team-oriented care for Spanish-speaking children/families with orofacial clefts (Edwards and Bonilla, 2004). They found that 10% of the responding teams treated 26% to 56% of Spanish-speaking patients.…”
Section: Resultsmentioning
confidence: 99%
“…In a second study, Edward and Bonilla (2004) examined team-oriented care for Spanish-speaking children/families with orofacial clefts (Edwards and Bonilla, 2004). They found that 10% of the responding teams treated 26% to 56% of Spanish-speaking patients.…”
Section: Resultsmentioning
confidence: 99%
“…Coordination between surgeons and other providers including pediatrics may need to be streamlined for both syndromic patients and patients with government insurance. With respect to gender, ethnicity, race, and language barriers, cleft care teams should use Spanish-specific language messaging and conduct outreach initiatives, which have been shown to increase local community education and empower families to seek care (Edwards & Bonilla, 2004). Other studies suggest that delayed cleft surgery may relate to cultural differences, mistrust of medical providers, financial inability to pay, or caregiver characteristics, which are not captured by the present study (Massenburg et al, 2016; Yao et al, 2016; Bennett et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not uncommon for members of cleft palate teams to encounter patients who speak primarily Spanish while many team members do not. In 2004, Edwards and Bonilla [2] reported survey results showing that Spanish speakers represented at least 25% of the patients seen by 16% of the responding cleft palate teams.…”
Section: Introductionmentioning
confidence: 99%